Translated Transcripts From Covert Recordings Used for Evidence in Court: Issues of Reliability - Gilbert, David; Heydon, Georgina (Frontiers in Communication, 2021)
Abstract Nation states increasingly apply electronic surveillance techniques to combat serious and organised crime after broadening and deepening their national security agendas. Covertly obtained recordings from telephone interception and listening devices of conversations related to suspected criminal activity in Languages Other Than English (LOTE) frequently contain jargon and/or code words. Community translators and interpreters are routinely called upon to transcribe intercepted conversations into English for evidentiary purposes. This paper examines the language capabilities of community translators and interpreters undertaking this work for law enforcement agencies in the Australian state of Victoria. Using data collected during the observation of public court trials, this paper presents a detailed analysis of Vietnamese-to-English translated transcripts submitted as evidence by the Prosecution in drug-related criminal cases. The data analysis reveals that translated transcripts presented for use as evidence in drug-related trials contain frequent and significant errors. However, these discrepancies are difficult to detect in the complex environment of a court trial without the expert skills of an independent discourse analyst fluent in both languages involved. As a result, trials tend to proceed without the reliability of the translated transcript being adequately tested.